Theology in a Post-Pandemic Age - Pernia, Antonio M. (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2023)
This essay is an attempt to explore the impact of the global Covid-19 pandemic on the Church and, in this context, to reflect on the question of how theology should be done in a post-pandemic age. It is divided into three parts: first, a reflection on the significance of the Covid-19 pandemic; secondly, a further reflection on the impact of the pandemic on the mission of the Church; and thirdly, an exploration into how theology should be undertaken in a post- pandemic age. It proposes that theology in a post-pandemic age should be done in HUMILITY, METAPHOR, SOLIDARITY, DIALOGUE, and with a view to MISSION. It is hoped that such a theology will shape and promote a Church whose mission will help build our world not on the basis of power, control, competition and the accumulation of wealth, but on tenderness, com- passion, solidarity and the sharing of resources.